Making an E-Pocket Book Based on the Isolation Study of Endophytic Bacteria of Laban Plants That Produce Secondary Metabolite Compounds as Enrichment Material for Natural Material Chemistry Courses - Anwar, Lenny; Linda*, Roza; Adisman, Rendika; Futra, Dedi; Alimin, Masnaini (Universitas Syiah Kuala, 2024)
This research addresses the need for effective teaching materials in natural materials chemistry courses, specifically focusing on secondary metabolite compounds derived from endophytic bacteria of laban plants. The main objective is to develop a valid e-pocket book that serves as an enrichment resource for lecturers and students. This study used a research and development approach using the 4-D model, which includes the stages of defining, designing, developing, and disseminating. However, this research was limited to the development stage. The E-Pocket Book was assessed for validity through various aspects, including content feasibility, presentation, grammar, graphics, appearance, and software utilisation. Validation involved feedback from material and media validators, as well as responses from chemistry education lecturers and students. Results showed that the E-Pocket Book achieved a highly valid category with an overall average score of 98.785% across the six assessment aspects. Feedback from chemistry education lecturers showed excellent criteria, with scores of 87.50% for content appropriateness and for usefulness, and 91.67% for ease of use. Similarly, student feedback reflected high satisfaction, with scores of 86.67% for ease of use, 85% for benefits of use and 83.09% for attractiveness of presentation. In conclusion, the developed E-Pocket Book was validated as a practical and effective teaching material for secondary metabolite compounds, demonstrating its potential to enhance the learning experience in natural materials chemistry courses. This study highlights the importance of incorporating user feedback in the development process to ensure materials meet educational needs and preferences